SIMILARITIES AND DIFFERENCES OF TRANSITIVE AND INTRANSITIVE VERBS IN ENGLISH AND UZBEK LANGUAGES - Navruza Karimova; Aziz Mukhamadiev (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: Verbs are essential components of sentences that convey actions, processes, or states of being. Understanding the distinction between transitive and intransitive verbs is crucial for constructing clear and grammatically correct sentences in English and other languages. Transitive verbs require a direct object to complete their meaning, while intransitive verbs do not need a direct object to make sense. Understanding the distinction between transitive and intransitive verbs helps writers and speakers construct grammatically correct sentences, identify the relationships between verbs and their objects, and convey precise meanings in their communication. Mastery of transitive and intransitive verbs enhances language proficiency and clarity in writing and speaking.